1975
DOI: 10.1111/j.1399-3054.1975.tb03784.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Auxin Protectors XII. Auxin Protectors and Polyphenol Oxidase in Developing Coffee Fruit

Abstract: Tbe fruit of the coffee plant {Coffea arabica) was analyzed for auxin protector content. Ripe coffee berries were separated into pit and pulp, ground in buffer, and assayed for auxin protectors. The extracts were then subjected to gel filtration in order to determine tbe molecular weight of the protector(s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The presence of caffeic acid could have resulted from the hydrolysis of chlorogenic acids occurring when fresh coffee pulp is piled, dried or extracted under conditions that favour chemical changes. It is interesting to note that Griffin and Stonier (1975) never found caffeic acid and chlorogenic acid together in the same extract of coffee pulp.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of caffeic acid could have resulted from the hydrolysis of chlorogenic acids occurring when fresh coffee pulp is piled, dried or extracted under conditions that favour chemical changes. It is interesting to note that Griffin and Stonier (1975) never found caffeic acid and chlorogenic acid together in the same extract of coffee pulp.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies in ripening coffee fruit, characterised by the presence of large quantities of chlorogenic and caffeic acid, showed that natural protector activity was invariably and singularly associated with chromatographic spots which exhibited a blue fluorescence under UV (Griffin & Stonier, 1975).…”
Section: Discussionmentioning
confidence: 94%
“…Although auxin is essential for the initiation of adventitious roots (Haissig 1974), comparative studies with cuttings from juvenile and adult plants have not provided evidence that it is the auxin level that limits rooting in adult plants (Hackett 1988), Starting with Hess (1962), considerable research has been done on rooting factors. Even though the chetnical identity of some of these factors is unclear, most exhibit the characteristics of phenols (Haissig 1986) and affect the peroxidase-catalysed oxidation of indoleacetic acid (IAA) (Griffin andStonier 1975, Lee et al, 1981),…”
Section: Introductionmentioning
confidence: 99%